2003
DOI: 10.1039/b305347d
|View full text |Cite
|
Sign up to set email alerts
|

Layer-by-layer self-assembled multilayers of redox polyelectrolytes and gold nanoparticles

Abstract: Construction and characterization of structural and charge transport properties of electrostatically LbL self-assembled multilayers of gold nanoparticles and a viologen-based redox-active polyelectrolyte is reported.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0
2

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 17 publications
1
41
0
2
Order By: Relevance
“…[18][19][20][21][22][23] The existing studies have demonstrated that multilayer GNP films as advanced functional materials are quite different in optical and electric properties from bulk gold. [13,14,25] Layer-by-layer (LbL) assembly that is based on the alternate adsorption of oppositely charged species has been a powerful technique for preparing multilayer GNP films because of its simplicity, flexibility, and effectiveness. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In addition to dithiols and PAH, proteins can serve as effective linking agents for the fabrication of multilayer thin films of GNP/protein nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…[18][19][20][21][22][23] The existing studies have demonstrated that multilayer GNP films as advanced functional materials are quite different in optical and electric properties from bulk gold. [13,14,25] Layer-by-layer (LbL) assembly that is based on the alternate adsorption of oppositely charged species has been a powerful technique for preparing multilayer GNP films because of its simplicity, flexibility, and effectiveness. [13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] In addition to dithiols and PAH, proteins can serve as effective linking agents for the fabrication of multilayer thin films of GNP/protein nanocomposites.…”
Section: Introductionmentioning
confidence: 99%
“…The absorption maxima of these bands (l max ) were fixed at a wavelength of 542 nm and did not change with the number of dipping cycles. Previous reports [21][22][23][24][25][26][27] have pointed out that in multilayer gold nanoparticles, strong interactions between neighboring dipolar particles can readily take place, which cause a red shift in l max with increasing number of dipping cycles and/or generate a new absorption band at a longer wavelength. In our case, however, no such features appear in the spectra, as shown in Figure 2, suggesting that the gold nanoparticles in films are spatially separated from each other, probably because of the long PLGA chains attached to the gold nanoparticles, and that the interparticle interactions are relatively weak.…”
Section: Resultsmentioning
confidence: 99%
“…The LbL assembly takes advantage of the same attractive forces that form complexes but in a controlled manner that produces thin, conformal films that can coat a variety of surfaces and thus are a powerful method for fabricating multilayer gold nanoparticle films. [15][16][17][18][19][20][21][22][23][24][25][26][27] In spite of these many reports, to the best of our knowledge, well-controlled gold nanoparticle assemblies guided with a polypeptide network have not yet been reported. The aim of this article is to construct homogeneously well-ordered gold nanoparticle multilayers assisted with a b-sheet peptide template.…”
Section: Introductionmentioning
confidence: 98%
“…Na Figura 2b, observa-se que o crescimento da arquitetura supramolecular de PAH/FtTsCo é progressivo e linear, o que acarreta em etapas de deposição uniformes. 12,13,19,20,22 Resultados similares foram encontrados nos sistemas PAH-AuNP/ FtTsNi, 41 (Figura 3). 20,43,44 Processos irreversíveis envolvendo ftalocianinas metálicas são comuns devido, principalmente, a efeitos de agregação da espécie FtTsCo(II) na superfície do eletrodo.…”
Section: Deposição Das Multicamadas Pah/fttscounclassified
“…7,8 A automontagem ganhou atenção especial devido a vantagens tais como fácil manipulação, baixo custo operacional, reprodutibilidade, versatilidade dos materiais utilizados e elevado controle da arquitetura molecular. 2,[9][10][11][12][13][14][15][16][17][18][19][20] Diversos materiais têm sido empregados na técnica LbL visando construção de filmes nanoestruturados, como metaloftalocianinas, 1,2,11-31 porfirinas, [32][33][34] polímeros condutores, 1,10 diazo-resinas, 15 nanopartículas metálicas 3,16,35 e moléculas biológicas. 14,16,17 Em especial, compostos de coordenação, quando imobilizados em filmes LbL, apresentam comportamento químico diferenciado quando comparados em solução e no estado sólido, situações nas quais efeitos supramoleculares devem ser levados em consideração.…”
Section: Introductionunclassified